2006
DOI: 10.1002/app.24727
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and mechanical and viscoelastic properties of rubbery epoxy/organoclay montmorillonite nanocomposites

Abstract: The morphology and mechanical and viscoelastic properties of rubbery epoxy/organoclay montmorillonite (MMT) nanocomposites were investigated with wideangle X-ray scattering (WAXS), transmission electron microscopy (TEM), tensile testing, and dynamic mechanical thermal analysis. An ultrasonicator was used to apply external shearing forces to disperse the silicate clay layers in the epoxy matrix. The first step of the nanocomposite preparation consisted of swelling MMT in a curing agent, that is, an aliphatic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…For the epoxy thermoplastic systems, several studies were reported. Boukerrou et al22 obtained significant increases in both the stiffness and the energy at break on epoxy‐octadecylammonium modified MMT nanocomposites. The organophilic modification of clay affects the final morphology of nanocomposites on three levels.…”
Section: Introductionmentioning
confidence: 99%
“…For the epoxy thermoplastic systems, several studies were reported. Boukerrou et al22 obtained significant increases in both the stiffness and the energy at break on epoxy‐octadecylammonium modified MMT nanocomposites. The organophilic modification of clay affects the final morphology of nanocomposites on three levels.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the nanoclay particles with very high aspect ratio can improve the modulus of the thermoplastic polymer. [16][17][18][19][20][22][23][24] The increment of the modulus depends on the morphology of nanocomposites. [24][25][26] The reinforcing efficiency of the nanofiller is balanced by two opposite phenomena.…”
Section: Resultsmentioning
confidence: 99%
“…Different types of polymers used in association with MMT for development of nanocomposites are polystyrene,6 poly ( N ‐vinylcarbazole),7 and epoxy resins 8–12. Studies on phase morphology, mechanical, and viscoelastic properties of exfoliated epoxy/MMT nanocomposite have been reported 13, 14. Pelissou et al15 have described the electrical and thermal characterization of nanocomposites consisting of an epoxy matrix containing micrometric quartz and small amount of nanoclay.…”
Section: Introductionmentioning
confidence: 99%